2008
DOI: 10.1159/000182821
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoepidemiological Profiles and Outcomes during First Hospital Admission of Head Injury Patients in Ikeja, Nigeria

Abstract: Background: Although head injury (HI) is a major public health problem in Nigeria and other low and middle income countries of the world, there is a paucity of data from these societies. This is largely due to under-reporting. We carried out a prospective study of the clinicoepidemiological profiles and outcomes following the first hospitalization of a cohort of head-injured patients in Ikeja, Nigeria, a metropolitan African city. Methods: In an 8-month period from May until December 2005, data from all HI cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 28 publications
5
41
0
Order By: Relevance
“…The proportion of patients who died during ICU admission is similar to 56% reported by a study in Kenya. [26] Other studies of severe head injury patients presenting to tertiary hospitals in other African countries [27] and in other centers in Nigeria [28] have reported higher mortality rates in the range of 70-90%. When contrasted with much lower mortality rates in more affluent societies, which are in the range of 16-38%, [18,29,30] these findings underscore the impact of severe head injury on the most economically active populations of LMIC and the importance of putting in place effective accident prevention and injury control measures and organized trauma care systems, which are currently lacking in many of these countries, Nigeria inclusive.…”
Section: Outcome Analysismentioning
confidence: 99%
“…The proportion of patients who died during ICU admission is similar to 56% reported by a study in Kenya. [26] Other studies of severe head injury patients presenting to tertiary hospitals in other African countries [27] and in other centers in Nigeria [28] have reported higher mortality rates in the range of 70-90%. When contrasted with much lower mortality rates in more affluent societies, which are in the range of 16-38%, [18,29,30] these findings underscore the impact of severe head injury on the most economically active populations of LMIC and the importance of putting in place effective accident prevention and injury control measures and organized trauma care systems, which are currently lacking in many of these countries, Nigeria inclusive.…”
Section: Outcome Analysismentioning
confidence: 99%
“…Nearly similar findings were observed by Bruns et al who concluded that male gender and young adults are at increased risk of succumbing traumatic brain injury compared to female and other age groups. 3,4 The study findings revealed that 63 (14.8%) of the study population deteriorated within 24 hours of observation and 3 (0.7%) died. As the level of consciousness on admission was decreasing; deterioration increased i.e., 12.7%, 16.7% and 33.3% with GCS of 15, 14 and 13 respectively.…”
Section: Discussionmentioning
confidence: 88%
“…Males (68%) predominate amongst the patient population, male:female ratio 2:1, whereas the overwhelming majority of the carers of the patients were females, 73%, male:female ratio 1:3. This may be partly because much of the grave neurosurgical disease profiled in this study is due to neurotrauma and the young, probably more adventurous males are known to be more prone to injury than their female counterparts in this part of the world (12). It may also be another affirmation of that apparent trend where females are the more likely of the two genders to be seen available caring for their wards in hospital settings (13).…”
Section: Discussionmentioning
confidence: 93%